2016
DOI: 10.1128/aac.00365-16
|View full text |Cite
|
Sign up to set email alerts
|

A Multinational, Preregistered Cohort Study of β-Lactam/β-Lactamase Inhibitor Combinations for Treatment of Bloodstream Infections Due to Extended-Spectrum-β-Lactamase-Producing Enterobacteriaceae

Abstract: The spread of extended-spectrum-␤-lactamase (ESBL)-producing Enterobacteriaceae (ESBL-E) is leading to increased carbapenem consumption. Alternatives to carbapenems need to be investigated. We investigated whether ␤-lactam/␤-lactamase inhibitor (BLBLI) combinations are as effective as carbapenems in the treatment of bloodstream infections (BSI) due to ESBL-E. A multinational, retrospective cohort study was performed. Patients with monomicrobial BSI due to ESBL-E were studied; specific criteria were applied for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
111
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 33 publications
6
111
1
1
Order By: Relevance
“…More recently, Gutiérrez-Gutiérrez et al conducted a multinational, observational study investigating this question in a design similar to the Rodriguez-Baňo study [52]. In fact, some of the same patients were included in both cohorts.…”
Section: Piperacillin-tazobactammentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Gutiérrez-Gutiérrez et al conducted a multinational, observational study investigating this question in a design similar to the Rodriguez-Baňo study [52]. In fact, some of the same patients were included in both cohorts.…”
Section: Piperacillin-tazobactammentioning
confidence: 99%
“…Existing observational data have indicated contradictory results between outcomes of patients receiving PTZ and carbapenems for the treatment of ESBL infections (Table 5) [8,47,[48][49][50][51][52][53][54]. Rodriguez-Baňo and colleagues provided some of the earliest robust data evaluating β-lactam-β-lactamase inhibitors (βL-βLIs) and carbapenems for the treatment of ESBL bacteremia by conducting a post hoc observational study of Spanish patients from 6 cohorts [47].…”
Section: Piperacillin-tazobactammentioning
confidence: 99%
“…In the past, the inoculum effect observed in vitro (1,2), data from animal studies (3,4), coexpression of additional ␤-lactamases not effectively inhibited by ␤-lactamase inhibitors (␤LI) (5), and concerns regarding inadequate pharmacokinetic-pharmacodynamic drug target attainment with standard ␤-lactam (␤L)/␤LI dosing regimens (6, 7) have tempered the enthusiasm for prescribing these agents for the treatment of invasive ESBL infections. However, more recently, and in large part due to the multicenter efforts led by several Spanish investigators (8,9), such concerns have been largely alleviated. It has been shown that for many patients with invasive ESBL infections, ␤L-␤LI treatments are safe and effective options.…”
mentioning
confidence: 99%
“…The investigators compared ␤L/␤LIs to carbapenems in a cohort of neutropenic patients with ESBL bacteremia and hematological malignancies. This is a subgroup that had traditionally been left unaddressed in previous observational studies (8,9,(11)(12)(13)(14)(15). The investigators used propensity-score matching to limit bias from confounding by indication.…”
mentioning
confidence: 99%
“…25,26 However, according to recent data, BLBLIs, if active in vitro, appear to be as effective as carbapenems for empirical therapy of bloodstream infections due to ESLB-Enterobacteriaceae, regardless of the source and specific species, if used at appropriate doses. 27 Therefore, high dosage with loading dose and semicontinuous administration of BLBLIs, supported by therapeutic drug monitoring should be preferred for clinically stable patients. is likely to result in treatment failure (even with in vitro susceptibility).…”
Section: Targeted Treatment Extended-spectrum-b-lactamases-producing mentioning
confidence: 99%